2013
DOI: 10.18632/oncotarget.1370
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 overexpression increases malignant potential of human glioma cells through Id1

Abstract: Increased COX-2 expression directly correlates with glioma grade and is associated with shorter survival in glioblastoma (GBM) patients. COX-2 is also regulated by epidermal growth factor receptor signaling which is important in the pathogenesis of GBMs. However, COX-2 expression has not been previously shown to directly alter malignancy of GBMs. Id1 is a member of the helix-loop-helix (HLH) family of transcriptional repressors that act as dominant-negative inhibitors of basic-HLH factors. This factor has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Recently, COX2 and PGE 2 have been implicated in cancer progression but mixed results were obtained with COX2 inhibitors and radio-sensitization [34, 35]. Our results provide a molecular mechanism, by which PGE 2 can sustain tumor growth and proliferation after tumor irradiation and support new alternative targets, such as EP2, to potentiate the effect of radiotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, COX2 and PGE 2 have been implicated in cancer progression but mixed results were obtained with COX2 inhibitors and radio-sensitization [34, 35]. Our results provide a molecular mechanism, by which PGE 2 can sustain tumor growth and proliferation after tumor irradiation and support new alternative targets, such as EP2, to potentiate the effect of radiotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…In our observational study, treatment with 500 µmol/l NaHS for 24 h obviously promoted protein COX-2 secretion in PLC/PRF/5 hepatoma cells. Importantly, accumulating evidence has demonstrated that cyclooxygenase (COx)-2 is overexpressed in several types of cancers cells (73)(74)(75) including hepatocellular carcinoma (HCC) (76). COX-2 expression in cells and animal models is closely associated with tumor cell growth and is a crucial molecule in the development of malignant tumors, including promotion of angiogenesis (77), anti-apoptotic effects (78), invasiveness of tumor cells (74), and tumor cell proliferation (79), demonstrating that COX-2 pathway is implicated in NaHS-induced PLC/PRF/5 hepatoma cell proliferation, anti-apoptosis, angiogenesis and migration.…”
Section: Discussionmentioning
confidence: 99%
“…[46] Furthermore, increased COX-2 expression has been shown to directly correlate with glioma grade and to be associated with shorter survival in glioblastoma multiforme patients. [47] In addition, there are data that COX-2 regulates the proliferation of glioma stem like cells. [48] (2) Promising antitumour activity of meloxicam has been demonstrated in prostate [49] and colorectal [50] cancer cell lines, hepatocellular carcinoma [51] and osteosarcoma.…”
Section: Long-term Experimentsmentioning
confidence: 99%